2016
DOI: 10.1038/srep33303
|View full text |Cite
|
Sign up to set email alerts
|

Spin excitations in hole-overdoped iron-based superconductors

Abstract: Understanding the overall features of magnetic excitation is essential for clarifying the mechanism of Cooper pair formation in iron-based superconductors. In particular, clarifying the relationship between magnetism and superconductivity is a central challenge because magnetism may play a key role in their exotic superconductivity. BaFe2As2 is one of ideal systems for such investigation because its superconductivity can be induced in several ways, allowing a comparative examination. Here we report a study on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
3
19
0
Order By: Relevance
“…A study of the magnetic structure of the honeycomb antiferromagnet Co 4 Nb 2 O 9 using the single-crystal diffractometer SENJU revealed that the magnetic structure is different from that proposed previously, but it better explains the magnetic properties as well as the magnetoelectric response of this compound [153]. In the following, we show in greater detail a recent inelastic scattering study on magnetic fluctuations in iron-based superconductors performed using the 4SEASONS spectrometer [48].…”
Section: Study Of Magnetism In Condensed Matters By Neutron Scatterinmentioning
confidence: 69%
See 3 more Smart Citations
“…A study of the magnetic structure of the honeycomb antiferromagnet Co 4 Nb 2 O 9 using the single-crystal diffractometer SENJU revealed that the magnetic structure is different from that proposed previously, but it better explains the magnetic properties as well as the magnetoelectric response of this compound [153]. In the following, we show in greater detail a recent inelastic scattering study on magnetic fluctuations in iron-based superconductors performed using the 4SEASONS spectrometer [48].…”
Section: Study Of Magnetism In Condensed Matters By Neutron Scatterinmentioning
confidence: 69%
“…These features of the instrument were originally designed for studies of high-critical-temperature (high-T c ) oxide superconductors. Indeed, copper and iron-based superconductors are still major research targets at 4SEASONS [44][45][46][47][48][49]. Including these materials, strongly correlated electron systems and magnetism dominate 80% of the experimental proposals.…”
Section: D-space Access Neutron Spectrometer 4seasonsmentioning
confidence: 99%
See 2 more Smart Citations
“…The [001] axis is parallel to the incident beam, and the [100] axis is on the horizontal plane and perpendicular to the incident beam. This configuration is similar to those often employed in measurements of 2D systems [10][11][12][13]. The incident energy (E i ) is 71 meV, and the rotating frequency of the Fermi chopper ( f ) is 250 Hz.…”
Section: Outline and Conditions Of Simulationmentioning
confidence: 99%